Lark Rise to Candleford. The complete season one [videorecording (DVD)] - Hallinan, Olivia, 1985-; French, Dawn; Sawalha, Julia, 1968-; Smith, Liz, 1921-2016; Coyle, Brendan (BBC Video ; Warner Home Video [distributor], 2009)
Follows the relationship of two contrasting communities: Lark Rise, a small hamlet gently holding onto the past, and Candleford, a neighboring market town bustling into the future. When young Laura Timmins leaves Lark Rise for a job at the Candleford post office, she discovers an eye-opening, exciting new world. In the face of scandals and feuds, she must leave her childhood behind.